2004
DOI: 10.1074/jbc.m309950200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hyaluronan and Reactive Oxygen Species in Tissue Kallikrein-mediated Epidermal Growth Factor Receptor Activation in Human Airways

Abstract: In human airways, oxidative stress-induced submucosal gland cell hypertrophy and hyperplasia, histological features of chronic bronchitis, have been linked to epidermal growth factor receptor (EGFR) activation. To explore mechanisms of oxidative stress-induced EGFR activation and signaling, primary cultures of human tracheal submucosal gland (SMG) cells were used to assess EGFR ligand release, EGFR phosphorylation, p44/42 MAPK phosphorylation, and mucin 5AC synthesis in response to reactive oxygen species gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
81
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 46 publications
6
81
0
Order By: Relevance
“…We have recently shown that Hyals 1, 2, and 3 are expressed in airway epithelium as well as in NHBE cells grown at the ALI. We found that Hyal protein expression is increased in the epithelium of asthmatics (26), suggesting that HA fragmentation during inflammatory responses could be due, in addition to ROS (15,21) to Hyal. In in vitro assays in cell-free conditions, ROS formation is fast and…”
Section: Hyaluronan (Ha)mentioning
confidence: 90%
See 4 more Smart Citations
“…We have recently shown that Hyals 1, 2, and 3 are expressed in airway epithelium as well as in NHBE cells grown at the ALI. We found that Hyal protein expression is increased in the epithelium of asthmatics (26), suggesting that HA fragmentation during inflammatory responses could be due, in addition to ROS (15,21) to Hyal. In in vitro assays in cell-free conditions, ROS formation is fast and…”
Section: Hyaluronan (Ha)mentioning
confidence: 90%
“…We have previously reported that ROS induce HA fragmentation (21,23), and that Hyal1, 2, and 3 are expressed in the airway epithelium (26). We and others (26,47) have shown that Hyal2 is selectively increased in inflammatory conditions and that TNF-␣ and IL-1␤ induce Hyal2 gene and protein expression in NHBE cells (26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations